2010
DOI: 10.1111/j.1399-3054.2010.01403.x
|View full text |Cite
|
Sign up to set email alerts
|

Epibrassinolide induces changes in indole-3-acetic acid, abscisic acid and polyamine concentrations and enhances antioxidant potential of radish seedlings under copper stress

Abstract: In the present study, the effects of epibrassinolide (EBL) on indole‐3‐acetic acid (IAA), abscisic acid (ABA) and polyamine (PA) tissue concentrations and antioxidant potential of 7‐day‐old Raphanus sativus L. cv. ‘Pusa chetki’ seedlings grown under Cu stress were investigated. EBL treatment alone or in combination with Cu enhanced free and bound IAA titers when compared with the metal alone. Modest increases in free and bound ABA contents were observed for EBL treatment alone. However, the combination of EBL … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
33
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 63 publications
5
33
1
Order By: Relevance
“…There occurs crosstalk between BRs and abscisic acid which is helpful in stress alleviation. Our results are supported by the results of Choudhary et al [26]. They observed an enhancement in the endogenous content of abscisic acid in Raphanus sativus under Cu stress with the application of EpiBR.…”
Section: -Epibrassinolide Mediated Regulation Of Endogenous Contentsupporting
confidence: 93%
See 2 more Smart Citations
“…There occurs crosstalk between BRs and abscisic acid which is helpful in stress alleviation. Our results are supported by the results of Choudhary et al [26]. They observed an enhancement in the endogenous content of abscisic acid in Raphanus sativus under Cu stress with the application of EpiBR.…”
Section: -Epibrassinolide Mediated Regulation Of Endogenous Contentsupporting
confidence: 93%
“…Negative effects of Cu stress on shoot and root weight of Hordeum vulgare and Sinapis alba were observed by Gvozdenac et al [24], and on shoot weight of Phaseolus vulgaris were observed by Ashagre et al [25]. We observed an improvement in the [26] in the seedlings of Raphanus sativus. Cu adversely affects the plant growth which subsequently reduces the plant biomass in terms of reduced shoot and root weights.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Therefore, it is possible that plant brassinosteroids have sufficient affinity with the rat gluco-corticoid receptor protein to be connected to their signaling chain through the recognition of molecules expressed by the constitutive CaMV promoter inserted in the transformation construct. Brassinosteroids have been shown to induce tolerance to a wide range of abiotic stresses (Kagale et al, 2007;Bajguz, 2011;Sittayat et al, 2007;Arora et al, 2010a;Koh et al, 2007) through the activation of anti-oxidative stress systems (Arora et al, 2010b), as well as the enhanced synthesis of abscisic acid (Yuan et al, 2010), ethylene, salicylic acid (Divi et al, 2010), polyamines and indole-3-acetic acid (Choudhary et al, 2010(Choudhary et al, , 2011. Responses to stress in plants, moreover, are known to be activated by increased levels of auxins, which in turn determines feedback interaction with flavonoid synthetic patterns (Peer and Murphy, 2007;Lewis et al, 2011) and crosstalk with brassinosteroid transcription process (see Depuydt and Hardtke (2011) for an extensive review).…”
Section: Discussionmentioning
confidence: 99%
“…Recent advancement showed that abiotic and biotic stresses facilitate elevation in free PA content by exogenous application of BR which helps to mitigate Cu-oxidative stress [77,78]. Besides, BR treatment keeps up the ideal measure of spermidine fixation required for typical plant development and particularly enhanced the production of putrescine required for stress tolerance, however, diminishes the concentration of cadaverine which produces oxidative burst to balance substantial metal stress [79].…”
Section: Brs and Polyaminementioning
confidence: 99%